MENIMBANG RELASI GENDER DALAM KELUARGA (SEBUAH TELA’AH KRITIS-FILOSOFIS-HUMANISTIK) - Rohinah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2012)
The discourse of gender equality as promoted by the feminist movement isintended to criticize the practice of the tradition in which men dominate women in variouslines of life, including family life and more specifically is in relation to the child. Suchpatriarchialism gains legitimacy from many directions, including from the customary laws, traditions, and theological-philosophical. Apart from the discursive conflict, both sides that are opposite each other have the same attitude in treating their child to build a discourse concerning their rights to the child. In this condition, the child is as passive party, where he is just a dead object and has no contribution during the determination of the rights of parents over their children. Criticism also comes with a reverse way of thinking, which puts the child in an active position, the object of life, and contributes. The rights of fathers and mothers that have established and understood differently as in patriarchialism and feminism then reformulated. This reformulation leads to a new discourse that could be called a post-feminism.